RETRACTED: Exosome-Derived miR-486-5p Regulates Cell Cycle, Proliferation and Metastasis in Lung Adenocarcinoma via Targeting NEK2 - Hu, Huihui; Xu, Hangdi; Lu, Fen; Zhang, Jisong; Xu, Li; Xu, Shan; Jiang, Hanliang; Zeng, Qingxin; Chen, Enguo; He, Zhengfu (Frontiers in Bioengineering and Biotechnology, 2020)
Objective: This study aimed to describe the mechanism of exosome-derived miR-486-5p underlying the cell cycle and progression in lung adenocarcinoma (LUAD). Methods: Bioinformatics methods were applied for identifying the differentially expressed genes (DEGs) in the GEO-LUAD dataset, predicting where the potential target miRNA was expressed and exploring the corresponding downstream target mRNA. qRT-PCR was conducted to detect the levels of the target genes in cancer cells. Thereafter, a series of in vitro experiments were performed for cell activities evaluation, including CCK-8, EdU, colony formation assay and transwell. Besides, Western blot was applied to determine the protein levels of the migration and invasion-related factors (NEK2, E-cadherin, N-cadherin, Vimentin, MMP-2 and MMP-9). Dual-luciferase reporter gene assay was employed for validating the targeted relationship between the target genes. Furthermore, nude mouse transplantation tumor experiment was conducted to further validate the role of the target miRNA in tumor development, and immunohistochemistry was used for Ki67 detection and TUNEL was applied for cell apoptosis assay. Results: miR-486-5p was observed to be enriched in serum exosomes, and seen to be significantly down-regulated in cancer tissues as well as in cancer serum exosomes. It was proven that exosomes could release miR-486-5p, thus regulating LUAD progression and affecting cell cycle. Moreover, NEK2 was identified as a target of miR-486-5p both in vivo and in vitro. Enrichment analysis revealed that NEK2 was mainly activated in cell cycle and mitosis-related pathways. Meanwhile, NEK2 was found to present significant difference in different TNM stages. Furthermore, rescue experiments indicated that the inhibitory effect of miR-486-5p overexpression on LUAD progression could be abrogated when miR-486-5p and NEK2 were simultaneously up-regulated. Conclusion: Exosome-derived miR-486-5p is responsible for cell cycle arrest as well as the inhibition of cell proliferation and metastasis in LUAD via targeting NEK2.